Relación dialógica entre el profesorado senior y el profesorado novel universitario - Maria Luisa Rodríguez Moreno (LED Edizioni Universitarie, 2015)
The intergenerational relation in the European universities has evolved over the years. In the beginning was characterized for a hierarchical structure until more democratic situation. In this article is studied the dialogical relation between junior and senior professors to facilitate the learning of teaching and the adjustment to new critical moments. The author proposes the analysis of expectations, needs and projects for better orientation to the young professors and give practical suggestions about effective mentoring in Spanish universities. To ensure the teacher ability of socialization or adaptation to the real context of the university structure, which involves an inevitable dialectic based on expectations over the medium to long term, in line with the paradigm of socialization interactive, through which seniors and juniors teachers accepte mutually influences and changes. This will lead to a gradual and imperceptible enrichment, by which different cohorts of students will benefit. At the same time, advances in the development of mentoring novice teacher will be an endless source of ideas for applied research.